ANALISIS DAMPAK INFLASI TERHADAP TINGKAT KEMISKINAN DI SUMATERA UTARA - Manik, Septriana; Frisnoiry, Suci; Sitompul, Morrines Elfrida (Universitas Jambi, 2024)
Inflation has a significant impact on poverty levels in North Sumatra. This study aims to investigate the impact of inflation on poverty levels in North Sumatra. Inflation as a complex economic phenomenon, has significant implications for the social and economic conditions of people, especially those in poverty. The method used is descriptive quantitative by using secondary data and data analysis methods with linear regression analysis, normality test, multicollinearity test, heterokedastisitas test, autocorrelation test, and hypothesis test. The results of the analysis showed that inflation has a noticeable impact on the level of poverty in the region. This study provides important insights for government policy in designing strategies to reduce poverty levels in the area. In conclusion, the need for targeted and effective action to overcome the negative impact of inflation on poverty levels in North Sumatra.The primary implication of these findings is that in order to effectively eliminate poverty, the government must create and execute more focused measures to control inflation. This study also highlights how crucial it is to coordinate social and monetary policies in order to combat poverty. In order to reduce the detrimental effects of inflation on public welfare, especially in North Sumatra, appropriate and focused action is desperately needed